How did 15 degree come in the following equation.
http://dc474.4shared.com/download/8_...55515-f1b2071a
plz help.
thanks in advance
How did 15 degree come in the following equation.
http://dc474.4shared.com/download/8_...55515-f1b2071a
plz help.
thanks in advance
$\displaystyle \theta = \tan^{-1}{\left( \frac{1-\sqrt{3}}{1+\sqrt{3}}\right)}=\tan^{-1}{\left( \frac{1-\sqrt{3}}{1+(1)(\sqrt{3})}\right)}$
Using the formula: $\displaystyle \tan^{-1}(x)-\tan^{-1}(y)=\tan^{-1}{\left( \frac{x-y}{1+xy}\right)}$
we get $\displaystyle \theta= \tan^{-1}(1)-\tan^{-1}(\sqrt{3})= 45^{\circ}-60^{\circ}=-15^{\circ}$